Shock pulse from a sonoluminescing gas bubble - Lee, YP; Karng, SW; Jeon, JS; Kwak, HY (PHYSICAL SOC JAPAN, 1997)
The shock pulse emanating from a sonoluminescing gas bubble was calculated by using the analytical solutions of the conservation equations for the gas inside the bubble and the Kirkwood-Bethe hypothesis for the outgoing wave. The rise time and the magnitude of the pulse signal are in good agreement with the observed values, which may provide the approximate value of the gas pressure at near the collapse of the sonoluminescing gas bubble.
Keywords: SYNCHRONOUS PICOSECOND SONOLUMINESCENCE